European Ship Recycling Regulation Entry-Into-Force Implications of the Hong Kong Convention - Engels, Urs Daniel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This study provides an in-depth analysis of the Hong Kong Ship Recycling Convention as adopted in May 2009 and a thorough analysis of the overall status quo of ship recycling regulations. It investigates the lack of sufficient ratifications of the Convention from both a legal and an economic perspective. The first part of the study focuses on the history of the Convention$1 (Bs entry-into-force provision and the rationale behind it. Due to the fact that this provision provides a considerable additional obstacle to the Convention$1 (Bs becoming legally binding, in the second part the focus of the work shifts to unilateral action in this field. An overview of the legal environment of European ship recycling legislation is followed by an analysis and evaluation of a number of proposals by the European Commission attempting to tackle the problems of current ship recycling procedures. With a particular emphasis on (planned) European measures in this regard, the analysis$1 (Boverall message is one of cautious optimism.s
Introduction -- The Hong Kong Convention -- Entry-Into-Force Provision -- European Ship Recycling Regulation -- Conclusions and Perspectives.
Keywords: Law; Industrial organization (Economic theory).; Environmental economics; Law; Law of the Sea, Air and Outer Space; European Law; Environmental Economics; International Environmental Law; International Economic Law, Trade Law; Industrial Organization